Changing Priorities in Vaccinology: Antibiotic Resistance Moving to the Top - Tagliabue, Aldo; Rappuoli, Rino (Frontiers in Immunology, 2018)
Antimicrobial Resistance (AMR) is currently the most alarming issue for human health. AMR already causes 700,000 deaths per year. It is estimated that 10 million deaths due to AMR will occur every year after 2050. This equals the number of people dying of cancer every yearly in present times. International institutions such as G20, World Bank, WHO, UN General Assembly, EU, and the UK and USA governments are calling for new antibiotics. To underline this emergency, a list of antibiotic-resistant "priority pathogens" has been published by WHO. It contains 12 families of bacteria that represent the greatest danger for human health. Resistance to multiple antibiotics is particularly relevant for the gram-negative bacteria present in the list. The ability of these bacteria to develop mechanisms to resist treatment could be transmitted with genetic material, allowing other bacteria to become drug-resistant. Although the search for new antimicrobial drugs remains a top priority, the pipeline for new antibiotics is not promising, and alternative solutions are needed. A possible answer to AMR is vaccination. In fact, while antibiotic resistance emerges rapidly, vaccines can lead to a much longer lasting control of infections. New technologies, such as the high-throughput cloning of human B cells from convalescent or vaccinated people, allow for finding new protective antigens (Ags) that could not be identified with conventional technologies. Antibodies produced by convalescent B cell clones can be screened for their ability to bind, block and kill bacteria, using novel high-throughput microscopy platforms that rapidly capture digital images, or by conventional technologies such as bactericidal, opsono-phagocytosis and FACS assays. Selected antibodies expressed by recombinant DNA techniques can be used for passive immunization in animal models and tested for protection. Antibodies providing the best protection can be employed to identify new Ags and then used for generating highly specific recombinant Fab fragments. Co-crystallization of Ags bound to Fab fragments will allow us to determine the structure and characteristics of new Ags. This structure-based Ag design will bring to a new generation of vaccines able to target previously elusive infections, thereby offering an effective solution to the problem of AMR.